(untitled) (Ameghiniana, 2013)
A litle rostral portion assigned to a pseudodontomitid, is described. It comes from the late Eocene-lower Oligocene sediments at Vicecomodoro Marambio (Seymour) Island, Antarctica. This pseudodontornitid was one of the biggest flying birds so far discovered. This is the second record and is the oldest one in the Southern Hemisphere.